2014
DOI: 10.1093/cid/ciu053
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Patients Hospitalized With Influenza A Subtypes H7N9, H5N1, and 2009 Pandemic H1N1

Abstract: Hospitalization with H7N9 virus infection is associated with older age and chronic heart disease, and patients have a longer duration of hospitalization than patients with H5N1 or pH1N1. This suggests that host factors are an important contributor to H7N9 severity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

12
101
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(115 citation statements)
references
References 34 publications
12
101
1
1
Order By: Relevance
“…While the 2009 influenza pandemic caused a significant social and economic burden, the A(H1N1)pdm09 virus was not as virulent as other influenza viruses, such as A(H5N1) or A(H7N9) (14,17,18). Compared to infections with circulating seasonal influenza A and B virus strains, infection with A(H1N1)pdm09 virus was associated with more severe disease in some human studies (19) but with comparable disease in others (20,21).…”
mentioning
confidence: 97%
“…While the 2009 influenza pandemic caused a significant social and economic burden, the A(H1N1)pdm09 virus was not as virulent as other influenza viruses, such as A(H5N1) or A(H7N9) (14,17,18). Compared to infections with circulating seasonal influenza A and B virus strains, infection with A(H1N1)pdm09 virus was associated with more severe disease in some human studies (19) but with comparable disease in others (20,21).…”
mentioning
confidence: 97%
“…In addition, the INF A virus subtypes H7N9, H5N1, and H1N1 have been reported to have different LOS [18]. These varying LOS by study might be explained by different standards for admission and discharge at individual hospitals.…”
Section: Discussionmentioning
confidence: 96%
“…It was shown that wild bird IAVs can directly infect mammals with minimal or no clinical symptoms. Yet diff erent magnitude of seroconversion makes the monitoring of the mammalian infections caused by avian IAV diffi cult (Yamazaki et al, 2009;Yang et al, 2012;Reed et al, 2014;Wang et al, 2014;Yang et al, 2014;Huang et al, 2015). On the other hand, the risk of avian and human IAV reassortants formation in susceptible wild and domestic mammalian species attracted the attention of many investigators.…”
Section: Discussionmentioning
confidence: 99%